The Mobile Internet Contribution in Tourism - Daniela Garbin Praničević; Anja Križan; Judita Peterlin (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
Daily use of mobile devices has become one of many living standards. The number of Internet users is increasing annually. Along with the mobile devices rising number, the need for responsive design also rises. The purpose of this research is threefold: firstly, to clarify, secondly, to explore, and thirdly, to discuss the role of mobile Internet in achieving tourism, particularly hotel strategic goals. The elaboration will be based on the mobile internet traffic history, in Croatia and globally. In the accordance with the above stated the authors collected the relevant data sample. Examples are: website visits, websites user conversions, share of realized reservations and transactions made on the websites via mobile devices to verify the significance of mobile Internet traffic for the tourism business. The research findings have the potential to contribute to the tourism manager's level of awareness regarding the role of mobile internet in tourism and hotel business. As additional contribution, it will be discussed the forthcoming perspectives of the mobile internet traffics and mobile internet future trend.
Keywords: A22; M10; O00; Z32; 330; mobile Internet traffic; tourism; user experience